Evaluation of synergistic antimicrobial effect of vitamins (A, B1, B2, B6, B12, C, D, E and K) with antibiotics against resistant bacterial strains. (June 2018) - Shahzad, Shakeel; Ashraf, Muhammad Adnan; Sajid, Muhammad; Shahzad, Aqeel; Rafique, Azhar; Mahmood, Muhammad Shahid
Graphical abstract: Highlights: Vitamins E and K were most effective against Acinetobacter baumannii . Vitamin B2 was found to be most effective in synergism with antibiotics (ATBs) against MRSA. Vitamin K showed remarkable synergistic activity against A. baumannii but no or negligible synergism against MRSA. Further study is needed to investigate the mechanism of interaction of vitamins with ATBs and with bacteria. ATB therapy against highly resistant bacteria may be successful if ATBs are used in combination with vitamins. Abstract: Objectives: Multidrug-resistant (MDR) superbugs, including Acinetobacter baumannii and methicillin-resistant Staphylococcus aureus (MRSA), are a challenge for healthcare professionals. In this study, the synergistic activity of vitamins with antibiotics against resistant bacterial strains was evaluated. Methods: Synergistic effects between antibiotics and stock solutions of vitamins were evaluated by the Kirby–Bauer disk diffusion assay. Distilled water and propylene glycol were used as solvent for water-soluble and fat-soluble vitamins, respectively. Final concentrations of 10 mg/mL for each water-soluble vitamin [B1 (thiamine), B2 (riboflavin), B6 (pyridoxine), B12 (methylcobalamin) and C (ascorbic acid)] and 0.1 mg/mL for each fat-soluble vitamin [A (retinol), D (cholecalciferol), E (α-tocopherol) and K (menadione)] were used in combination with the antibiotics. Results: The results demonstrated that vitamins K and E had good synergistic activity with piperacillin/tazobactam, imipenem and doripenem against A. baumannii, whilst vitamins B1, B2 and B12 showed remarkable synergistic activity with linezolid against MRSA. Vitamin B1 was further shown to have better synergism with oxacillin, tetracycline, rifampicin and linezolid against MRSA. The fat-soluble vitamins E and K showed good synergism against Gram-negative A. baumannii, whilst the water-soluble vitamins B1, B2 and B12 were effective against MRSA but not against A. baumannii . Conclusions: This synergistic action of vitamins with antibiotics may be used as a tool to treat MDR superbugs, with further evaluation required at a molecular level.